Access to Modern Family Planning Services Among Adolecents in Kangai Town Council Dokolo District - Catherine Acen (Uganda Christian University, 2024)
This study examines the barriers to accessing modern family planning services among adolescents in Kangai Town Council, Dokolo District, Lango Region. It also explores the role of socio-cultural institutions in shaping access and attitudes toward these services, as well as strategies for promoting and sustaining positive views on family planning. Using a mixed-methods approach, data were collected from a sample of 320 participants through structured questionnaires and interviews. The findings reveal significant barriers, including physical inaccessibility, lack of tailored information, economic constraints, and stigma. Socio-cultural institutions, particularly religious and traditional leaders, play a crucial role in influencing access and attitudes toward family planning. While there is some community support, the study highlights the need for targeted interventions to improve accessibility and promote positive attitudes among adolescents.Recommendations include enhancing healthcare infrastructure, providing comprehensive education, and engaging socio-cultural institutions in advocacy efforts. The study contributes to understanding the complex factors affecting family planning access in rural settings, offering insights for policymakers and healthcare providers to improve service delivery for vulnerable populations.